2018
DOI: 10.1073/pnas.1809583115
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic antipairing of homologous and sex chromosomes via spatial restriction of two haploid sets

Abstract: SignificanceMitotic recombination must be prevented to maintain genetic stability across daughter cells, but the underlying mechanism remains elusive. We report that mammalian cells impede homologous chromosome pairing during mitosis by keeping the two haploid chromosome sets apart, positioning them to either side of a meridional plane defined by the centrosomes. Chromosome oscillation analysis revealed collective genome behavior of noninteracting chromosome sets. Male translocation mice with a maternal-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(62 citation statements)
references
References 70 publications
7
55
0
Order By: Relevance
“…How the 3 billion base-pair genomic DNA is organized in the nucleus has been a subject of extensive research. Previous imaging studies based on chromosome paintings elegantly demonstrated that each chromosome exists in a space termed chromosome territory (Cremer et al 2003;Bolzer et al 2005;Hua and Mikawa 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the 3 billion base-pair genomic DNA is organized in the nucleus has been a subject of extensive research. Previous imaging studies based on chromosome paintings elegantly demonstrated that each chromosome exists in a space termed chromosome territory (Cremer et al 2003;Bolzer et al 2005;Hua and Mikawa 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome territories have been studied by various chromosome imaging techniques (Cremer et al 2003;Bolzer et al 2005;Hua and Mikawa 2018).…”
Section: Spatial Organization Of Haploid Chromosomes In the Nucleusmentioning
confidence: 99%
“…It has been reported that the role of homologous recombination in promoting genomic instability might contribute to the occurrence and development of tumors, 74 hence homologous recombination should be tightly regulated in order to avoid genomic instability at mitosis. 75 Mismatch repair often results in microsatellite instability, which is one of two main mechanisms of genomic instability, and tumor predisposition. 76 NER, as one of four DNA repair systems, requires strict regulation to avoid genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the previous cytological analyses in a total of 154 regenerated plants from wheat × barley crosses (Koba et al 1991 ; Taketa et al 1995 , and our tests) as well as in primary plants of many other interspecific or intergeneric crosses (see references below) did not identify conspicuous (such as Robertsonian) translocations in somatic cells. Furthermore, parental chromosome complements in primary cereal hybrids are known to be spatially separated in the interphase (Schwarzacher et al 1989 ; Leitch et al 1990 ; Gernand et al 2005 ) and/or during mitoses (Finch et al 1981 ; Linde-Laursen and Jensen 1984 ; Leitch et al 1991 ; Mochida et al 2004 ), similar to human cells (Hua and Mikawa 2018 ; Reichmann et al 2018 ). Finally, the uniparental elimination of chromosomes is usually completed in the early embryo during a few initial cell divisions within a time window of 5–8 DAP (days after pollination) in H. vulgare × H. bulbosum (Subrahmanyam and Kasha 1973 ; Bennett et al 1976 ; Gernand et al 2006 ), 3–4 DAP in wheat × maize (Laurie and Bennett 1989 ) and 1–2 DAP in wheat × Imperata cylindrica crosses (Komeda et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%